Biomechanical and clinical evaluation of 3D-printed integrated tibial prosthesis for reconstructing AORI type Ⅲ tibial plateau defects - Wang, Yong; Zhou, Xiaoyu; Guo, Lin (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo compare the biomechanical stability and clinical efficacy of 3D-printed integrated tibial prosthesis (ITP) and traditional modular augment prostheses (MAP) in reconstructing AORI Type Ⅲ tibial plateau defects, and to provide a reference for clinical decision-making.MethodsA finite element model of AORI Type Ⅲ tibial plateau defect (defect area >60%, depth >20 mm) was established using CT data of a healthy male subject. Four groups of models were constructed: Spacer, Cone, Sleeve, and ITP. Under different loads (700N, 1750N, 2100N, 2450N, simulating standing, knee flexion, stair climbing, and jogging), the contact stress at the prosthesis-bone interface, vertical displacement of the tibial plateau, and relative micromotion were analyzed. Additionally, a retrospective study was conducted on 6 patients with AORI Type Ⅲ defects who underwent TKA with ITP between January 2021 and January 2025, with clinical evaluation using KSS scores, X-ray imaging, and gait analysis.ResultsBiomechanically, under all load conditions, ITP showed lower peak contact stress at the cortical bone, cancellous bone, and prosthesis interfaces (e.g., cortical bone stress at 2100N: 16.69 MPa for ITP vs 30.00 MPa for Spacer), smaller vertical displacement (245.6  μm at 2100N vs 385.2 μm for Spacer), and reduced relative micromotion (7.1  μm at 2100N vs 13.0 μm for Spacer). Clinically, the 24-month follow-up showed that the KSS score increased from 46.5 ± 4.8 preoperatively to 85.4 ± 5.5, with no loosening or osteolysis. Gait parameters (walking speed, step length, cadence) were significantly improved at 1 year postoperatively, and the affected side showed symmetry with the contralateral side. Due to the single-arm small sample size of the clinical cohort (n = 6) and the lack of a MAP control group, the clinical findings of this study are only preliminary observations.